Communicating health information to Pacific women : a thesis presented in partial fulfilment to the requirements for the degree of Masters of Business Studies in Communications Management at Massey University - Jameson, Anna Margaret (Massey University, 1997)
The ability to acquire and use information is an essential component in the process of obtaining knowledge. It is an interesting phenomenon that people do not always access information that is beneficial for them (Chatman, 1991). As New Zealand becomes increasingly multicultural the need to communicate health messages in a culturally appropriate and effective way is expanding in importance. This study examined the nature of current methods used by Pacific women to access cervical screening information. It also explored the barriers to obtaining that information and how the participants believed communication about cervical screening should take place to reach Pacific women in a culturally appropriate way. Results are analysed in the light of the knowledge gap hypothesis. This hypothesis places emphasis on socioeconomic factors as being predictors of knowledge. Twenty Pacific women living in Palmerston North were selected for the study using the snowball sampling technique. The participants varied in age from 20 to over 50 years and their education ranged from primary to tertiary level. The third key variable was length of time in New Zealand. This ranged from three months to 33 years. Semi-structured indepth interviews of approximately two hours duration were completed. These were recorded and transcribed with the permission of the participants. Transcripts were analysed using the technique of content analysis. The study found that knowledge gaps were related to the "subject matter". The topic of cervical screening was perceived to be very sensitive because of the taboo nature of discussing topics related to sex and the sexual organs. Sensitivity appeared to be related to age and length of time in New Zealand but not to education. Socioeconomic factors did not appear to be closely linked to levels of understanding by Pacific women about cervical screening. Interest in the topic and the motivation to acquire information were more indicative of knowledge gaps. Three key barriers to successful communication were identified: cultural background, lack of confidentiality and embarrassment. Of these, cultural background was perceived by the participants to have the most significant influence on their ability to access information. Face-to-face communication was the preferred method for obtaining both health information and cervical screening information. Print, radio or visual media communications were not considered effective due to the sensitivity of the subject and the indirect nature of the media. Written communication was advocated by the participants to supplement face-to-face communication when initially finding out about cervical screening. The study suggested that holding face-to-face meetings with a health professional present, was the most effective way of reaching Pacific women. The lack of research in the area of communicating with Pacific women about health information places greater emphasis on the importance of the findings of this study. It also highlights the need to develop a subsequent body of research to ensure communication is effective, appropriate and not misdirected.
Keywords: Information Services -- New Zealand; Women, Polynesian -- Health and hygiene; Women, Melanesian -- Health and hygiene; New Zealand; Transcultural medical care; Communication in medicine; National Cervical Screening Programme (N.Z.)